Transient analysis of hybrid SMA-FRP reinforced concrete beams under sequential impacts. (1st April 2020) - Shafei, Erfan; Kianoush, Reza
Highlights: Hybrid SMA-FRP reinforcement is a new approach for impact damage mitigation of concrete beams. The successively increasing residual deflections and localization of cracks cannot be reduced using steel reinforcement. Application of Hybrid SMA-FRP rebar minimizes the damage grade of concrete and enables post-impact deformation recovery. Balanced SMA-FRP volume ratio minimizes the peak and residual displacements for impact repeats. Hybrid SMA-FRP beams absorb high impact impulse and provide the service level stiffness. Abstract: Damage growth and plasticity under impact loads is a major concern in steel reinforced concrete (RC) structures. Yielding of steel reinforcements results in delay in repair of RC members after impacts and shock loads. In an effort to mitigate the impact-induced damage, this paper investigates numerically a hybrid type of reinforcing rebar made of fiber reinforced polymer (FRP) with integrated super-elastic shape memory alloy (SMA) fibers. Hybrid SMA-FRP rebar has both ductility and super-elasticity features, which is used to improve the sequential impact response in current work. Primarily, the experimentally validated constitutive models are used to simulate the transient response of RC beams. Moreover, hybrid SMA-FRP reinforced beams with various rebar ratios are modeled and subjected to sequential drop weight impacts. The results of regular and hybrid SMA-FRP reinforced beams are compared based on the damage growth, energy balance of materials, maximum and residual displacement, acceleration, and reaction forces. Numerical results show enhanced performance of SMA-FRP rebar in terms of energy dissipation and damage mitigation. The accumulation of concrete damage and rebar yielding resulted in increasing residual displacement in regular beams. However, super-elasticity of SMA and high strength of FRP lead to remarkable displacement recovery in hybrid SMA-FRP RC beams.